Prevalence and Antimicrobial Susceptibility of Escherichia coli and Klebsiella pneumoniae Isolated from the Tigris River, Baghdad, Iraq - Hussein, Israa Abd; Talib, Adel Hussain; Fakhry, Saad Sabah (Iraqi Journal of Science, 2025)
The presence of antimicrobials and antimicrobial-resistant bacteria (ARB), in the aquatic environment is becoming a cause of great concern as the possibility of the development of antibiotic-resistant pathogens, even superbugs, is increasingly posing problems to the environment and human health. The main objectives of this study were to analyse the antibiogram profile, calculate the multiple antibiotic resistance indices, and assess the co-occurrence of resistance to several antibiotics in the isolates. Samples were collected from four sites: S1 Al-Muthana Bridge, S2 Al-Sarrafia Bridge, S3 Al-Senak Bridge, and S4 Al-Jadriyah Bridge from November 2023 until July 2024. This investigation included 32 Escherichia coli and 18 Klebsiella pneumoniae bacterial isolates, confirmed both phenotypically and genotypically. The isolation of E. coli and K. pneumoniae is determined by membrane filtration techniques and biochemical analysis followed by the VITEK2. Polymerase chain reaction (PCR) was used to establish the identity of the propagated isolates by identifying the β-galactosidase gene with E. coli-specific lacZ3 primers, and the malate dehydrogenase mdh housekeeping gene. An antimicrobial susceptibility test was performed according to the Kirby-Bauer disk diffusion method against 15 selective antibiotics. The results showed E. coli exhibited complete susceptibility to Nitrofurantoin, Ampicillin, and Cefuroxime with average susceptibility (20%). While the susceptibility of K. pneumoniae was higher for: Nitrofurantoin, Ampicillin, Cefuroxime, Cefoxitin, Ceftazidime, Gentamycin, Amikacin and Imipenem with average susceptibility (53.3%) out of 15 antibiotics. In contrast, the results of resistance showed that most of the E. coli and K. pneumoniae isolates had a higher percentage of the resistance. Multiple antibiotic resistance (MAR) index values ranged from 33% to 93%, which indicates a high dose of the antibiotic used.